Effectiveness of Closed Reduction in the treatment of nasal bone fractures - Sigdel, Brihaspati; Sah, K (Nepal Medical College Journal, 2021)
This study was conducted to investigate the effectiveness of closed reduction of nasal bone fracture according to severity. It was a retrospective study carried on 60 patients with mean age of 30.2 years (range 10-67 years) who have undergone a closed reduction of a nasal bone fracture at Gandaki Medical College Teaching Hospital from January 2017 to December 2019. The patient with nasal bone fracture who underwent surgical intervention with closed reduction under General anaesthesia were included in this study. Fracture severity was evaluated according to Hwang et al.’s classification method. All patients underwent closed reduction with external nasal splinting under General anesthesia. The patients were followed-up for at least three months to assess the complications, such as fracture recurrence and functional abnormality in the Department. The most common cause of nasal bone fracture was road traffic accidents 25 (41.6%) followed by physical assaults 18 (30%), fall injuries 12 (20%), other incidences 3 (5%), and industrial accidents 2 (3%). Forty-three (72%) cases underwent closed reduction within 24 hours of those who arrived within 4-6 hour of nasal injury in the hospital and the remaining 17 (28%) cases were reduced after 5 days of trauma. Concurrent fracture found in 8 (13%) cases and it included maxillary, zygomatic, orbital, frontal bone fracture. Nasal bone fracture mostly occurs in road traffic accidents. Closed reduction with good alignment is the preferred method. Septorhinoplasty and extracorporeal septoplasty should be applied in difficult and comminuted nasoseptal fracture.